Overview of LabVIEW as a Graphical Programming Tool for Developing Industrial Technology Proficiency - Istoni, Reza; Chan, Yefri; Hasanah, Nur; Isniah, Sarah; Sumartono, Budi; Syofian, Suzuki; Setiyaningsih, Timor (Fakultas Teknik Universitas Darma Persada, 2025)
The purpose of this session is to expose participants with technical and vocational educational backgrounds to LabVIEW graphics programming software. In technical and industrial domains like biotechnology, aircraft, and telecommunications, LabVIEW is a commonly used system development tool. Hands-on practice and a demonstrative approach are used in the in-person instruction. LabVIEW's foundations, industrial applications, and hardware and software integration are all covered in the curriculum. The training results show that participants have a better understanding of visual programming and its possible uses in the business. This program is a component of a larger strategy to promote Industry 4.0-aligned technological literacy.